Ethanol poisoning and alcohol-related pathology of internal organs - E. N. Travenko (Кубанский научный медицинский вестник, 2016)
It was found that the incidence of alcohol-related diseases with fatal intoxications with ethanol on the background of the various forms of alcoholic liver disease is variable and is prevalent in the groups alcoholic hepatitis and steatosis.